2017
DOI: 10.4172/2329-8731.1000166
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Anti-Microbial Agents with Ascorbic Acid in Catheter Associated Urinary Tract Infection

Abstract: Background: Rapid development of microbial resistance is an emerging health care issue of developing countries. In this study we evaluated the susceptibility pattern of bacterial pathogens causing catheters associated urinary tract infection (CAUTI) against commonly prescribed antibiotics alone and in combination with ascorbic acid in institutional settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Combination of antibacterial drugs with ascorbic acid to enhance antibiotic activity was tested against a broad spectrum of uropathogenic bacteria [ 24 , 34 , 54 , 55 , 56 ]. Most of these studies verified the synergistic effect of ascorbic acid with fluoroquinolones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of antibacterial drugs with ascorbic acid to enhance antibiotic activity was tested against a broad spectrum of uropathogenic bacteria [ 24 , 34 , 54 , 55 , 56 ]. Most of these studies verified the synergistic effect of ascorbic acid with fluoroquinolones.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies verified the synergistic effect of ascorbic acid with fluoroquinolones. AA has been reported as an agent enhancing the effectiveness of ciprofloxacin (CIP) and ceftriaxone action in the treatment of CAUTIs induced by Candida sp., Citrobacter sp., E. coli , Enterobacter sp., and S. aureus [ 54 ]. Similarly, a combination of levofloxacin and ascorbic acid increased the reduction in biofilm formation by E. coli , Klebsiella sp., Citrobacter sp., Enterobacter sp., Proteus sp., and Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…ASC interaction with antibiotics and antibiotic resistance has also been documented: ASC had synergic effect with sulfonamides, trimethoprim, chloramphenicol, ampicillin, erythromycin and colistin in checkerboard assays on P. aeruginosa [ 4 ]; a 1-mM ASC treatment eliminates penicillinase plasmids from S. aureus , and reduces the MIC of penicillin and tetracycline [ 10 , 11 ]; a triple combination of ASC, apo-transferrin and imipenem was effective against carbapenem-resistant A. baumannii [ 9 ]; biofilm formation by P. aeruginosa was inhibited by ASC at 11–34 mM concentrations [ 6 ] and at 0.2–2 mM (possibly non-neutralized ASC; and also diminished piperacillin, ceftazidime, ciprofloxacin and gentamicin MICs [ 5 ]); but 2 mM ascorbate reduced the biofilm inhibitory activity of aminoglycosides gentamicin and amikacin [ 8 ]; addition of 10 mM ASC decreased the MIC of some antibiotics (e.g., ampicillin, tetracycline) and increased the MIC of others (e.g., erythromycin, ciprofloxacin) when testing S. aureus , several Streptococcus spp., and E. coli [ 12 ]. In non-PubMed-indexed journals reports are even more disparate (e.g., [ 13 , 14 , 15 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In general, vitamins may alter antimicrobial activity of particular antibiotics [8]. Carlsson et al (2005) [9] and Afzal et al (2017) [10] showed an increased antimicrobial activity of fluoroquinolones and aminoglycosides during AA addition. Habash et al (1999) [11] additionally proved that vitamin C decreases the adhesion and microorganisms colonization of the biomaterials used in diagnostic/treatment procedures involving the urinary tract.…”
Section: Introductionmentioning
confidence: 99%